Lost in cyberspace. (Economist, 1999)
Considers the computer scientists and programmers responsible for the Internet and the World Wide Web who failed to profit from its commercial exploitation. Development of Gopher at the University of Minnesota; National Centre for Supercomputer Applications (NCSA) development of a browser based on the web standard that had been developed at CERN; Identification of pioneers and their motives.